Estimation of excess mortality during COVID-19 pandemic based on death registry quality analysis. - Ferreira, Assel Muratovna Shigayeva; Moura, Lucas de Almeida; Paes, Neir Antunes (Seven Editora, 2023)
Background: There was a debate whether an accurate measurement of deaths was exacerbated during COVID-19 pandemic 2020 in Brazil. Purpose: This study aimed to analyze the magnitude and temporal course of excess mortality from the COVID-19 pandemic in 2020 with evaluation of mortality data quality in one state of Northeast region of Brazil. Methods: Excess mortality estimation and evaluation of the quality of COVID-19 death records during 2020 pandemic was applied for the state of Paraiba. The assessment of deaths records quality included analysis of its coverage and completeness (redistribution of garbage codes (GCs) with redistribution of ill-defined causes). Results: The total number of deaths due COVID-19 in Paraiba for 2020 increased by 37.4% after data quality correction analysis. The study proved statistically significant excess of deaths in the state for all-cause mortality and natural causes, with approximately 2-fold higher number for respiratory diseases. The quality data correction added significant fractions on top of initially observed deaths which makes the scope of exceeding deaths in Paraiba even larger. Conclusions. There is strong evidence that the full impact of the 2020 pandemic in Paraiba has been much greater than what is indicated by reported deaths due to COVID-19 alone. It is noteworthy that the methodology applied to the state of Paraiba can be replicated for any Brazilian state. DOI:https://doi.org/10.56238/emerrelcovid19-050